Effect of NH3 on structural and optical properties of SiO2-CuO core-shell nanostructure - Salim M.A.; Misran H.; Othman S.Z.; Shah N.N.H.; Razak N.A.A.; Manap A. (2023)
CuO nanoparticles at ca. 20-50 nm were successfully coated on monodispersed silica spheres prepared by modified sol-gel method. A renewable palm oil based decyl-alcohol (C10) was employed as nonsurfactant surface modifier prior to coating with CuO. Various amounts of ammonia (NH3) (0-1 ml) was as catalyst during the modification process to study the effect in homogeneous deposition of CuO on silica surfaces. The homogeneous depositions of CuO on silica were achieved with the addition of 0.9 ml of NH3. The optical absorption peak and energy band gap (Eg) values were at ca. 1.8-2.18 eV suitable for semiconductor and optical sensor materials. © (2014) Trans Tech Publications, Switzerland.